CARPAL TUNNEL SYNDROME IN CYCLISTS. Issue 1 (31st January 2017) - Sousa, Daniel; Sassul, Nicolás
Objectives: About a group of cyclists, professionals / amateurs, Mountain bike, road and triathlon; achieve a good diagnosis of the disease, with a good clinical examination and sectorized according EGM injury evoked potentials. Methods: Clinical examination and accurate test with different signs of pathology. EGM with evocative potential and conduction velocity. Results: After 25 track cyclists, 18 professionals, 22 male and 3 female; for 24 months. Through good clinical examination and EMG. We got that 70% had direct compression injuries Carpal tunnel for poor support on the handlebars. The rest were cervical praxis, by poor body position on the bike, taking cervico very steep angles / dorsal, during competitions or training for more than 2 hrs. Conclusion: A good prevention work with our teacher / cyclist in the position of deposrtista in ciclo simulador. Work in the gym, on tone and elongation of the upper limb. A good EGM, made with a specialist physiatrist. It leads to the correct diagnosis, leads to a good final treatment; which agreed that:* Cervical praxis, had good results with treatment Conservative / FST / vit.B12.* The Carpal tunnel own injuries, treatment was quirúrg. (Open surgery) with subsequent FST / vit..B12 with satisfactory return in time to sporting activity.